Ideengeschichte der Psychotherapie: Theorien, Konzepte, Methoden - Strauß, Bernhard; Galliker, Mark; Linden, Michael; Schweitzer, Jochen (Verlag W. Kohlhammer, 2021)
Psychotherapy has a long historical development, with a rich stock of theoretical concepts, tried and tested interventions, and clinical and scientific evidence. It is also constantly undergoing further evolution and differentiation. In the process, developmental contexts and solid knowledge may also occasionally be forgotten or ?rediscovered= using new terms, so that it is difficult to consolidate any overarching ?core knowledge= in psychotherapy. The purpose of this book is to present the current state of theory development and practice in relation to the four main psychotherapeutic procedures in the context of their historical development & and this may also counteract any occasional ?forgetting of history=. This is not a history book, however, but an up-to-date textbook that provides an overview of the foundations of psychotherapy across different procedures and schools.
Enthält 43 Beiträge
Literaturangaben
Keywords: Aufsatzsammlung; 1600-2021; Ideengeschichte; Methode; Psychotherapie